Therapeutic effect of diagnostic ultrasound on enzymatic thrombolysis - Basta, Giuseppina; Lupi, Cristiana; Lazzerini, Guido; Chiarelli, Piero; L’Abbate, Antonio; Rovai, Daniele (Thrombosis and Haemostasis, 2004)
If delivered at elevated intensity, ultrasound potentiates enzymatic clot dissolution; however, an elevated acoustic intensity damages vascular wall and favors reocclusion. This study’s aim was to investigate whether exposure to high-frequency, lowintensity ultrasound generated by a diagnostic scanner enhances enzymatic thrombolysis, and if this effect differs in clots from blood of normal subjects and of patients with coronary artery disease (CAD). Venous blood samples were drawn from 10 healthy volunteers and from 10 CAD patients on chronic medical treatment, which also included aspirin. Each sample generated 2 radiolabelled clots, which were positioned in 2 in vitro models filled with human plasma recirculating at 37°. One clot was exposed to acetyl salicylic acid (60 μg/ml), tissue plasminogen activator (3 μg/ml) and heparin (1 IU/ml), while the other was exposed to the same medications plus ultrasound (2.5 MHz, mechanical index = 1.0) for 3 hours. Enzymatic thrombolysis was measured as solubilization of radiolabel. Normal subjects and patients did not significantly differ as to coagulation parameters, weight, volume and density of the clots, and fibrinolytic activity (p = 0.794). Ultrasound exposure did not influence thrombolysis in clots of normal subjects (p = 0.367), while it enhanced the dissolution of clots of CAD patients (p = 0.013). The enhancement was equal to 51% at 5 minutes, 32% at 15 minutes, 27% at 30 minutes, 20% at 1 hour and 19% at 3 hours (p < 0.05). Diagnostic ultrasound enhances enzymatic dissolution of clots generated from the blood of CAD patients, likely due to chronic treatment and in particular to aspirin.
Keywords: Thrombosis; ultrasound; thrombolysis; microbubbles